2014
DOI: 10.14740/wjon736w
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Recurrence of Diffuse Large B-Cell Lymphoma in Sciatic Nerve

Abstract: Sciatica is a common clinical presentation with a number of etiological factors. Many of them are innocuous like prolapsed intervertebral disc or peripheral compression in the sciatic nerve. Occasionally the cause could be of a more serious nature like a nerve sheath tumor or more infrequently, lymphomatosis. We describe recurrent lymphoma in a patient who had been in remission presented with sciatica as result of the involvement of the nerve with metastatic tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Lymphoma is defined as a neoplastic proliferation of lymphoid cells from a secondary lymphoid structure, a lymph node or an extranodal structure. It is well established that extranodal site involvement is present in up to 40% of DLBCLs, and virtually any extranodal location can be a primary site [2] . However, peripheral nerve involvement in lymphomas is a rare manifestation, whether as an initial or recurrent presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphoma is defined as a neoplastic proliferation of lymphoid cells from a secondary lymphoid structure, a lymph node or an extranodal structure. It is well established that extranodal site involvement is present in up to 40% of DLBCLs, and virtually any extranodal location can be a primary site [2] . However, peripheral nerve involvement in lymphomas is a rare manifestation, whether as an initial or recurrent presentation.…”
Section: Discussionmentioning
confidence: 99%
“…It could be also the first manifestation of non-Hodgkin`s lymphoma in rare cases, which is called primary neurolymphomatosis. Peripheral nerve involvement may manifest as solitary or multifocal lesions and sciatic nerve is the most common site for lymphoma involvement [2] . In addition, cranial nerves or spinal roots may be involved by lymphatic infiltration [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, schwannomas are the most common peripheral nerve tumor, with an incidence of 0.3 to 0.4 cases per 100,000, and comprise 5% to 8% of all soft-tissue tumors 1 . Peripheral nerve lymphomas have been described as a dissemination of systemic disease or an extension of central nervous system involvement, but primary high-grade large B-cell lymphomas of the peripheral nervous system can occur and most frequently present in the sciatic nerve [2][3][4] .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the difficulty in the diagnosis of neurolymphomatosis, radiculopathy in the setting of positive history of lymphoma should raise clinical concern. Deivaraju et al reported a case of recurrent diffuse large B-cell lymphoma of the sciatic nerve first identified on a routine surveillance PET-CT 4 . Their patient began to develop symptoms of radiculopathy concurrent with the timing of surveillance imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation